Long‐Term Survival and Predictors of Failure of Opening Wedge High Tibial Osteotomy. Issue 4 (13th February 2023) - Guarino, Amedeo; Farinelli, Luca; Iacono, Venanzio; Cozzolino, Andrea; Natali, Simone; Zorzi, Claudio; Mariconda, Massimo
Abstract : Objective: High tibial valgus osteotomy (HTO) is a widely accepted procedure indicated for varus knee with symptomatic osteoarthritis of the medial compartment. However, there is a lack of studies evaluating long term results of this procedure. The primary aim of this study was to evaluate the long‐term survival of opening wedge high tibial osteotomy (HTO) for isolated osteoarthritis in the medial compartment of the knee. The secondary objective was to identify independent predictors of conversion to total knee arthroplasty (TKA). Methods: This is a long term retrospective study of 296 cases of open wedge HTOs performed at a single center (level of evidence IV) between January 2005 and August 2015. Opening wedge medial HTO was always performed after diagnostic arthroscopy. Eighty‐three percent of the population (233 patients, 247 procedures) was followed up at a mean 11.6 years (6–17) by telephone interview, to evaluate the possible conversion to TKA. Mean age at the index operation was 42.8 years (range 15–70) and most patients were male (70%). Associated procedures (e.g., platelet rich plasma supplementation, microfractures, meniscectomy, etc.) were carried out at the time of the HTO in 80 (32%) cases. Survival of HTO and its association with age, sex, body mass index, smoking habit, preoperative severity of varus deformity, cartilage status at surgery, and associated procedures were evaluated. Kaplan–Meier and Cox regression analyses were performed. Results: Thirty‐three of the 247 HTOs (13.4%) were converted to knee replacement, with 86.6% of the original procedures surviving at a mean 12‐year follow‐up. Kaplan–Meier survival estimates at 17 years for HTO were 75.5% (95% confidence interval [CI] 66.7–84.3). There was significant difference ( P < 0.001) in the 17‐year survival rate between obese (55.5%; 95% CI 35.3–75.6) and non‐obese (79.7%; 95% CI 70.1–89.2) patients. The determinants of conversion to knee arthroplasty detected at multivariate Cox regression analysis were body mass index, severity of cartilage degeneration in the medial compartment (Outerbridge grade), and age. Conclusion: The long‐term survival of open wedge HTO for osteoarthritis in the medial compartment of the knee is satisfactory. The risk of conversion to TKA is significantly increased in obese patients. Advanced age and severity of pre‐existing cartilage damage may also contribute to the risk of conversion to TKA. Abstract : The long‐term survival of open wedge HTO for osteoarthritis in the medial compartment of the knee is satisfactory. The risk of conversion to TKA is significantly increased in obese patients. Advanced age and severity of pre‐existing cartilage damage may also contribute to the risk of conversion to TKA.